TEKNIK PENGUMPULAN DATA DALAM PENELITIAN - Iis Maesaroh; Ully Arta Miladia; Millah Fithriyan; Lukman Nulhakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The quality of scientific research is largely determined by the accuracy of the data collection techniques employed. This article provides an in-depth examination of data collection methods based on the methodological perspective of John W. Creswell, a prominent figure in the field of research methodology. The analysis focuses on the three principal approaches developed by Creswell: quantitative, qualitative, and mixed methods. In the quantitative approach, Creswell emphasizes the use of surveys, experiments, and validated measurement instruments to produce statistically analyzable data. The qualitative approach highlights in-depth interviews, participant observation, and document analysis as tools to understand the subjective meanings of human experiences. Meanwhile, the mixed methods approach allows for the systematic integration of quantitative and qualitative data to gain a more comprehensive understanding of research phenomena. The findings indicate that Creswell’s framework offers a comprehensive methodological guide, enabling researchers to select the most appropriate techniques based on research objectives, context, and complexity. Thus, understanding Creswell’s approach plays a vital role in designing research that is valid, reliable, and meaningful.